Analisis Impor Pakaian Bekas Terhadap Kerusakan Ekologi Ghana dalam Perspektif Ekologi Politik - Sinka, Amira Kanaya; Dewi, Putu Ratih Kumala; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
With the rapid growth of the clothing trade, the consumerism rate for new clothes is also increasing. Therefore, the second-hand clothing trade has become a hot commodity, especially for developing countries that are willing to accommodate second-hand clothing. Ghana is one of the developing countries with high poverty rate. Therefore, second-hand clothing has become an alternative for Ghanaians to fulfil their clothing needs, making it one of the largest imported commodities in Ghana. However, the massive import of second-hand clothing in Ghana has caused major ecological impacts. This study uses political ecology theory to look at the impact of textile waste from the second-hand clothing trade in Ghana. The result in this study find out that the import of second-hand clothing causes textile waste that is difficult to decompose, difficult to deal with and to control it, which has an impact on the environment and the people of Ghana who depend on clean water and sanitation. This is because the Ghanaian government has lax regulations to deal with the import of second-hand clothing, plus Ghana's cooperation with various developed countries which causes Ghana to accept the import of secondhand clothing from these countries. Keywords: Ghana, Second-hand Clothing, Imports, Environment, Trade